ANALISIS KESULITAN SISWA MAN DALAM MENYELESAIKAN SOAL OPEN ENDED PADA MATERI BARISAN ARITMATIKA - Ade Kurniawan; Sanapiah; Nurul Azmi; Dwi Utami Setyawati (Jurnal Ilmiah Mandalika Education (MADU), 2023)
Abstract :this study aims to describe the difficulties experienced by high school students in solving open ended questions on arithmetic sequences. As for the type of research used in this research is descriptive qualitative research. The subjects used in the study consisted of 2 high-ability students, 2 moderate-ability students and 2 low-ability students. The research instruments used consisted of tests and interviews. As for the results of data analysis, there were 2 students with high abilities, 1 person had no diddicurlty in solving the question,whie 1 other person had difficulty solving question number 2. While for moderate ability there were 2 students able to describe the problem but still wrong and not finished, whereas students who have low abilities have difficulties in solving the questions thoroughly because none of the students are able to answer questions properly and correctly, it is difficult to understand the intent or meaning of the questions given, and they are only able to explain what is known and what is being asked. While the results of this study stated that students with high abilites had no mistakes in solving word problems, for moderate abilites there were a number of things that needed to be improved, especially the operation part, whilw low abilities has difficulties in understanding the concept of algebraic operations. So it can be concluded that students who have 85%, medium ability as ,much as 70% and low ability as much as 55%.